Storytelling as a Discursive Strategy for Framing Fragile and Stable States in WHO Reports (International Journal of Language, Literacy and Translation, 2024)
The embedding of personal stories in formal reports allows for the dissemination of complex information alongside relatable narratives which are more palatable. Storytelling serves to humanize information, making it more accessible and impactful for diverse audiences. This paper examines the use of storytelling as a discursive strategy employed by the World Health Organization (WHO) to report the responsiveness of both stable and fragile states to the COVID-19 pandemic. By analyzing personal stories which were included in extensive reports published for global consumption, this paper explores how storytelling was utilized as a discursive strategy to convey stereotypical images of stable and fragile states. The analysis revealed that the personal stories consistently portrayed fragile states as incapable of managing the crisis without external support. In contrast, stable states were portrayed as being very much in control of the situation, equipped with the best people and facilities to deal with the pandemic. The paper argues that besides serving as a powerful tool to humanize a global crisis, personal stories also serve to construct separate identities for stable and fragile states. Employing a content analysis, it was found that the personal stories went beyond narratives about the pandemic also to highlight broader issues in fragile states, such as gender discrimination. In so doing, the stories were reinforcing mainstream media narratives which typically portray fragile states as being backward. The findings inform media practitioners, particularly those working in the healthcare sector, about the integration of storytelling in official reports.